2011
DOI: 10.1177/0886109911405491
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Muslims in Four Western Countries Post—9/11

Abstract: This qualitative study explored the experiences of 34 Muslim individuals in four Western countries to gain a better understanding of their experiences with prejudice and discrimination following the terrorist attacks of September 11, 2001. An intersectional lens reveals the interlocking nature of identity, oppression, and privilege, and the findings provide insights into what helps affected individuals and communities be resilient in the face of persistent anti-Muslim sentiment. The social work profession is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…The rate of schizophrenia in Muslims is similar to that of non-Muslims (Al-Issa, 2000) but high rates of post traumatic syndrome disorder (Abu-Ras & Abu-Bader, 2009); and depression (Sheridan, 2006); and stress (Barkdull et al, 2011). Suicide is strictly forbidden in Islam and international studies in Pakistan, Malaysia and Saudi Arabia, showed low suicide rates prevalence (Al-Khathami, 2001;Murty et al, 2008;Zakiullah et al, 2008).…”
Section: Muslim and Mental Health Problemsmentioning
confidence: 90%
“…The rate of schizophrenia in Muslims is similar to that of non-Muslims (Al-Issa, 2000) but high rates of post traumatic syndrome disorder (Abu-Ras & Abu-Bader, 2009); and depression (Sheridan, 2006); and stress (Barkdull et al, 2011). Suicide is strictly forbidden in Islam and international studies in Pakistan, Malaysia and Saudi Arabia, showed low suicide rates prevalence (Al-Khathami, 2001;Murty et al, 2008;Zakiullah et al, 2008).…”
Section: Muslim and Mental Health Problemsmentioning
confidence: 90%
“…Although Islam phobia has deep historical bearing in the United States, many of the participants recounted stories of feeling generally socially accepted prior to 9/11 (Barkdull, Khaja, et Al., (2011). A significant number of women recalled the attacks of 9/11 as having an impact on their identity as Muslims.…”
Section: Self-perceptionmentioning
confidence: 99%
“…The Islamophobia (a term that first emerged in Britain to describe an intense fear or an aversion to Muslim people (Runnymede, 1997) is intensified after this date (Barkdull et al, 2011).…”
Section: Signs Of Discrimination Aggravated After September 11mentioning
confidence: 99%
“…Muslims in Western report as the media has influenced their lives, fueling hostility, hatred, and resentment among non-Muslims (Ahmad, 2006;Khiabany & Williamson, 2008;Barkdull et al 2011). …”
Section: Signs Of Discrimination Aggravated After September 11mentioning
confidence: 99%